Application of a biological‐based nanomagnetic catalyst in the synthesis of bis‐pyrazols and pyrano[3, 2‐c]pyrazoles. (6th October 2016) - Zolfigol, Mohammad Ali; Navazeni, Mahdiyeh; Yarie, Meysam; Ayazi‐Nasrabadi, Roya
Abstract : {Fe3 O4 @SiO2 @(CH2 )3 ‐thiourea dioxide‐SO3 H/HCl}, a newly reported nanomagnetic core–shell supported solid acid catalyst, was successfully employed in the preparation of 4, 4′‐(arylmethylene)bis(1 H –pyrazol‐5‐ol) and pyrano[3, 2‐ c ]pyrazole derivatives. The presented methods are very efficient and high‐yielding. Also, the catalyst exhibited powerful potential for reusability in both types of reactions. Abstract : {Fe3 O4 @SiO2 @(CH2 )3 ‐thiourea dioxide‐SO3 H/HCl}, a newly reported nanomagnetic core–shell supported solid acid catalyst, was successfully employed in the preparation of 4, 4′‐(arylmethylene)bis(1 H –pyrazol‐5‐ol) and pyrano[3, 2‐ c ]pyrazole derivatives. The presented methods are very efficient and high‐yielding. Also, the catalyst exhibited reusability in both reactions.